Bullseye: shotgun metagenomics taking aim at the microbial diversity associated with tubes of Ceriantharia - Ceriello, Hellen [UNESP]; Brito, Gustavo R. [UNESP]; de Oliveira, Bruno Francesco Rodrigues; Cunha, Marielton dos Passos; Stampar, Sérgio N. [UNESP] (Springer Nature, 2024)
This study aimed to analyse the microbial biodiversity in ceriantharian tubes through shotgun metagenomics, to enhance the understanding of ecological dynamics in these microhabitats. We sampled two tubes of Ceriantheomorphe brasiliensis in Florianópolis (SC), and two tubes of Ceriantheopsis lineata in Alcatrazes archipelago (AK), South and Southeast Brazil, respectively. The environmental DNA from the tubes was extracted, amplified, and submitted to shotgun metagenomics sequencing on the Illumina HiSeq platform, and the biodiversity analysis was run using the Kraken2 software. Our results indicate that Ceriantharia-associated microbiomes likely harbour novel microbial diversity, as roughly only 8% of metagenomic reads were classified. Microbial composition was highly similar in both locations, with the Bacteria domain predominating, particularly the phyla Pseudomonadota and Actinomycetota. Nitrososphaerota was consistently the most common archaeal phylum in all samples. The bacterial classes Betaproteobacteria and Planctomycetia, and the archaeal class Nitrososphaeria were present in all four tubes, as were the bacterial family Pseudomonodaceae and the archaeal family Nitrosopumilaceae. Roseobactereaceae dominated alphaproteobacterial families from AK tubes, while Streptomycetaceae prevailed among actinobacterial families from SC tubes. The α-diversity indicates similar values between AK and SC samples, with slight distinctions favouring SC. β-diversity results show higher similarity within the same locations (AK or SC) than between different locations, highlighting spatial influence on microbial composition. To the best of our knowledge, this study is the first to address microbial composition found in ceriantharian tubes, using shotgun metagenomics, and our findings set up the scenario for a wider comprehension of these cnidarians as key holobionts in marine ecosystems.
Keywords: Anthozoa; eDNA; Eukaryote; Kraken2; Microbiome; Prokaryote